The Argentine economy - Ferrer, Aldo. (Berkeley : University of California Press, 1967)
The book seeks to analyze the economic formation of Argentina using a historical approach for a systematic and broad understanding of the problems of national development and , therefore, the framing of a policy to strengthen the economic structure, to accelerate the rate of development, and raise the living standard of the population. The book is expected to stimulate empirical research and an analysis of Argentine development.
Includes index
Bibliographical footnotes.
rpm 14/06/2017
Loans
Keywords: Argentine -- Economic Conditions; Argentine Economy; Argentina